Ryanodine receptor modification and regulation by intracellular Ca2 + and Mg2 + in healthy and failing human hearts. (March 2017) - Walweel, K.; Molenaar, P.; Imtiaz, M.S.; Denniss, A.; dos Remedios, C.; van Helden, D.F.; Dulhunty, A.F.; Laver, D.R.; Beard, N.A.
Abstract: Rationale: Heart failure is a multimodal disorder, of which disrupted Ca 2 + homeostasis is a hallmark. Central to Ca 2 + homeostasis is the major cardiac Ca 2 + release channel – the ryanodine receptor (RyR2) – whose activity is influenced by associated proteins, covalent modification and by Ca 2 + and Mg 2 + . That RyR2 is remodelled and its function disturbed in heart failure is well recognized, but poorly understood. Objective: To assess Ca 2 + and Mg 2 + regulation of RyR2 from left ventricles of healthy, cystic fibrosis and failing hearts, and to correlate these functional changes with RyR2 modifications and remodelling. Methods and results: The function of RyR2 from left ventricular samples was assessed using lipid bilayer single-channel measurements, whilst RyR2 modification and protein:protein interactions were determined using Western Blots and co-immunoprecipitation. In all failing hearts there was an increase in RyR2 activity at end-diastolic cytoplasmic Ca 2 + (100 nM), a decreased cytoplasmic [Ca 2 + ] required for half maximal activation ( K a ) and a decrease in inhibition by cytoplasmic Mg 2 + . This was accompanied by significant hyperphosphorylation of RyR2 S 2808 and S 2814, reduced free thiol content and a reduced interaction with FKBP12.0 and FKBP12.6. Either dephosphorylation of RyR2 using PP1 or thiol reduction using DTT eliminated any significant difference in the activity of RyR2 from healthy and failing hearts. We also report a subgroup of RyR2 in failing hearts that were not responsive to regulation by intracellular Ca 2 + or Mg 2 + . Conclusion: Despite different aetiologies, disrupted RyR2 Ca 2 + sensitivity and biochemical modification of the channel are common constituents of failing heart RyR2 and may underlie the pathological disturbances in intracellular Ca 2 + signalling. Highlights: Human failing heart ryanodine receptor 2 (RyR2) Ca 2+ release channels display an altered regulation to cytoplasmic Ca 2+ . Alterations in failing heart RyR2 function are correlated with higher RyR2 phosphorylation and thiol modification, and lower FKBP association. Observed changes in RyR2 function and protein modifications would contribute to the diastolic leak phenotype in heat failure.